2013
DOI: 10.1371/journal.pone.0082455
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Malaria Parasitemia and Anemia among Hospitalized Children in Rakai, Uganda

Abstract: BackgroundThere is a paucity of data on malaria among hospitalized children in malaria endemic areas. We determined the prevalence, presentation and treatment outcomes of malaria and anemia among children in two hospitals in Rakai, Uganda.MethodsChildren under five years hospitalized in Kalisizo hospital or Bikira health center in Rakai district, Uganda between May 2011 and May 2012 were enrolled and followed-up until discharge, death or referral. Data were collected on social-demographic characteristics, curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 25 publications
(32 reference statements)
4
22
4
Order By: Relevance
“…Significant reductions in anaemia prevalence have been achieved or recorded following malaria control programs in endemic areas. Low prevalence of anaemia found in this study differs with that of Kiggundu et al (2013) who reported a high prevalence of anaemia (56.3%) among children under-five in Southwestern Uganda [26]. Furthermore, this finding contrasts a higher prevalence of anaemia among children under-five years in Navrongo, Northern part of Ghana [10].…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…Significant reductions in anaemia prevalence have been achieved or recorded following malaria control programs in endemic areas. Low prevalence of anaemia found in this study differs with that of Kiggundu et al (2013) who reported a high prevalence of anaemia (56.3%) among children under-five in Southwestern Uganda [26]. Furthermore, this finding contrasts a higher prevalence of anaemia among children under-five years in Navrongo, Northern part of Ghana [10].…”
Section: Discussioncontrasting
confidence: 96%
“…The Jasikan District situated in the Volta Region of Ghana is located in the malaria-endemic zone and might have contributed to the increased proportion of malaria with anaemia cases as compared to Western Ghana. On the contrary, this finding is comparatively lower than the 76.8% prevalence reported in children under-five years from a survey conducted in Southwestern Uganda [26]. Higher prevalence reported in Uganda could be attributed to multifactorial causes such as hookworm and nutritional deficiencies including the location of the district in a malaria-endemic zone.…”
Section: Discussioncontrasting
confidence: 58%
“…This difference was borderline significant. This is not in agreement with a study in Uganda, 15 which showed that confirmed malaria was lower among girls (52.3%) than boys (57.3%), and it had no bearing on the effect of helminth coinfection (data not shown).…”
Section: Discussioncontrasting
confidence: 86%
“…Malaria, a disease caused mainly by Plasmodium falciparum, is a major public health concern in sub-Saharan Africa (Menard et al, 2013). All age groups are affected but the most vulnerable are children aged five years and below, pregnant women and people living with HIV/AIDS (Kiggundu et al, 2013). Many studies have shown that malaria is influenced by the environment such as climate change and is often linked to developmental projects of hydro-agricultures whose implementation disregards their impacts on malaria transmission (Koudou et al, 2007).…”
Section: Introductionmentioning
confidence: 99%